Ethical consumption and Iceland: A review of current literature and an exploratory study - Pezzini, Giada, 1981- (2013)
The ecological impact of society depends largely on consumer activities. All the phases of consumption - production, delivery, purchase, use and disposal of products – have repercussions on the environment, as well as on the larger society. For this reason sustainable production and consumption are central elements in the debate about sustainable development. This final project consists of two parts. Part 1 is a six-chapter review of obstacles which have been found to hamper ethical consumption. The paper focuses on Iceland in specific, and reviews the state of ethical consumption in Iceland and the barriers to its diffusion. Finally, a number of possible avenues of action are described and reviewed, with an eye on the Icelandic situation. Part 2 consists of a paper presenting the findings of an original research on ethical concerns among Icelandic consumers. The paper was presented at Þjóðarspegillinn XIII 2012, the annual social science research conference of the University of Iceland, on October 26, 2012.